2018
DOI: 10.1016/j.nuclphysb.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Shannon entropy and particle decays

Abstract: We deploy Shannon's information entropy to the distribution of branching fractions in a particle decay. This serves to quantify how important a given new reported decay channel is, from the point of view of the information that it adds to the already known ones. Because the entropy is additive, one can subdivide the set of channels and discuss, for example, how much information the discovery of a new decay branching would add; or subdivide the decay distribution down to the level of individual quantum states (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Furthermore work of Ref. [52,53] has shown that Gibbs-Shannon entropy is constituted for devising distributions through the decays of hadrons and assessing the information relating to the new decay channel added to it.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore work of Ref. [52,53] has shown that Gibbs-Shannon entropy is constituted for devising distributions through the decays of hadrons and assessing the information relating to the new decay channel added to it.…”
Section: Introductionmentioning
confidence: 99%
“…[23]. Information entropy has been found to be quite successful in the investigation of new decay modes of the Higgs-Boson [24] and particles [25,26] at the LHC, axion mass evaluation [27], and has also been recently applied in studying SUSY models [28,29]. In earlier studies, it has been shown that features of the Higgs-Boson in Split-SUSY resemble the SM Higgs-Boson and therefore distinction between these may be quite challenging in experiments [30].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, to the right of the diagram, the parton fragments into an identified hadron and the Shannon entropy of the fragmentation function is the focus and first goal of this work as well as that of a companion article [5] on which it is based. Other works cited therein and in [6] have dealt with the entropy intrinsic to the distribution of the decaying products for the unstable hadrons formed in a collision, particularly of the Higgs boson, and other applications. Let us quickly recall the concepts of Shannon entropy and Kullback-Leibler divergence.…”
Section: Introductionmentioning
confidence: 99%